the Pengaruh alat peraga mesin pembagian berbasis Realistic Mathematic Education (RME) terhadap pemahaman konsep siswa pada materi operasi pembagian di kelas VII SMP Yayasan Perguruan IRA - Tarigan, Adelia Br; Sibarani, Mikhael Agus Tua; Silvina, Nur; Tarigan, Putri Br; Tampubolon, Rafael; Simbolon, Stevania Sri Debbye Br; Siregar, Budi Halomoan (Universitas Sarjanawiyata Tamansiswa, 2025)
The problem found is the low understanding of concepts on division operation material. This is due to the difficulty of understanding the abstract material. This is triggered by the lack of utilization of relevant learning media to overcome it. This study examines the effect of RME-based division machine props on the conceptual understanding of division among seventh-grade students at SMP Yayasan Perguruan IRA. This research design uses a pre-test and post-test control group as part of a quasi-experimental research method with a quantitative approach. The population of this study was all seventh-grade students, with a sample of 18 students in the control class and 18 in the experimental class. In the post-test, the control and experimental classes obtained sig <0.05, so it was stated that there was a significant difference between the experimental class and the control class. Thus, the study results showed a substantial effect in applying Realistic Mathematic Education (RME)-based division machine props on understanding the concept of division operations in class VII of SMP Yayasan Perguruan IRA. The findings highlight the practical effect of RME-based teaching aids in improving students' conceptual understanding and emphasize the need for scalable, inclusive teaching aids in mathematics education.